Impact of an electronic documentation system on timeliness and ancillary task completion - Samuel Strong; Judy Huang; Heather Nelkin; Amar Ramudhin; Claudia M Goldblatt; Craig A Greszler (American Journal of Health-System Pharmacy, 2026)
Abstract Purpose This study was conducted to compare the completion rate of ancillary tasks associated with sterile compounding and the timeliness of documentation before and after implementation of a technology-assisted workflow (TAWF) and electronic documentation software solution. Methods This mixed methods, pre-post study was conducted at 3 related facilities (sites A, B, and C). Sterile and nonsterile compounding records were evaluated using both electronic data and ethnographic observations over two 90-day periods. The workflow before and after implementation was assessed for percentage of ancillary tasks completed, timeliness of completion, percentage of storage area inspections completed, and time required to document compliance activities. Results Analysis indicated that while sites B and C saw significant improvement in on-time completion of ancillary activities, site A did not. Site B increased its on-time completion from 42.3% of all activities to 79.1%, while site C increased the completion rate from 72.1% to 98.1% (P < 0.0001 for both comparisons). Similarly, sites B and C increased the percentage of completed medication storage area inspections both overall and across the majority of evaluated subcategories. Timely completion of inspections remained relatively consistent at all 3 sites; site A saw a slight increase. Finally, the total time that staff used to document ancillary compounding activities declined by 6 to 92 seconds at each of the 3 sites during the postimplementation period. Conclusion Implementation of mobile technology with a new TAWF system can meaningfully increase timeliness and visibility of documentation of ancillary compounding tasks, leading to improvements in standardization, documentation, and operational efficiency.